2016
DOI: 10.1016/j.jsv.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of a cantilever beam with a closed, embedded horizontal crack including local flexibilities at crack tips

Abstract: As one of major failure modes of mechanical structures subjected to periodic loads, embedded cracks due to fatigue can cause catastrophic failure of machineries.Understanding the dynamic characteristics of a structure with an embedded crack is helpful for early crack detection and diagnosis. In this work, a new three-segment beam model with local flexibilities at crack tips is developed to investigate the vibration of a cantilever beam with a closed, fully embedded horizontal crack, which is assumed to be not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 58 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…The parameters such as the crack closure effect, stress ratio, SIF range, critical SIF, and the threshold of SIF are considered for the model of crack growth, which is called the modified Forman Model [21]. This model is employed for crack growth analysis in this study and shown as…”
Section: The Modified Forman Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters such as the crack closure effect, stress ratio, SIF range, critical SIF, and the threshold of SIF are considered for the model of crack growth, which is called the modified Forman Model [21]. This model is employed for crack growth analysis in this study and shown as…”
Section: The Modified Forman Equationmentioning
confidence: 99%
“…Ruotolo et al [15] analyzed the dynamic response of a cracked beam under harmonic forcing by using a so-called closing crack model to represent the cracked element. Liu et al [21] proposed a three-segment beam model having local flexibilities due to cracks to analyze the dynamic response of a beam having a closed, fully embedded crack. Shih and Chen [22] examined the coupling effect of the fatigue crack growth and dynamic response of a cracked shaft with straight-edge or elliptical arc cracks considered.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, many scholars have devoted themselves to studying the nonlinear properties of the concrete compressive stress-strain relationship and exploring the reasonable, mathematical expression between stress and strain [14].…”
Section: Concrete Constitutive Relationmentioning
confidence: 99%
“…Cao et al [12] conducted two, static tests of post-tensioned, bonded, prestressed concrete beams in two stages of fatigue tests and analyzed the change in the nonlinear, dynamic characteristics of the beam's damage. Jia et al [13] introduced the results of the bending test in the four-part, prestressed, ultra-high strength concrete beam to evaluate the effect of the prestressed, tendon depth and area on the bending behavior of the beam Liu et al [14] developed a new three-segment beam model with local flexibilities at crack tips to investigate the vibration of a cantilever beam with a closed.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the material nonlinearity of the concrete Liu et al (2016) developed a mathematical model to investigate the influence of cracks on the dynamic behavior of a cantilever beam. For this purpose, they developed a model with local flexibility at the crack tips to analyze the beam vibrations.…”
Section: Introductionmentioning
confidence: 99%